Irrigation and soil fertility management practices - Keraita, Bernard N.; Cofie, Olufunke O. (2014)
This chapter describes the different irrigation methods and nutrient application practices used by urban vegetable farmers. Data are based on surveys conducted in Kumasi, Accra and Tamale. Recent relevant publications are also reviewed.